2006
DOI: 10.1515/znc-2006-5-615
|View full text |Cite
|
Sign up to set email alerts
|

Does DNA Methylation Pattern Mark Generative Development in Winter Rape?

Abstract: In this paper we report on changes in DNA methylation pattern in rape apices and leaves during transition from vegetative to reproductive stage due to grafting and/or vernalization. Grafted plants of winter rape (Brassica napus L., var. "Gó rczań ski") (stock from vernalized, scion from non-vernalized plants) were used together with vernalized non-grafted plants. In addition, methylation status was determined also in spring rape (var. "Młochowski") grown under normal and low temperature. The methylation-sensit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
3
2

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 19 publications
1
10
0
Order By: Relevance
“…These results confirmed the authors' previous analysis, which suggested the presence of MSAP loci with changes in the methylation state specific for vernalization and a significant prevalence of demethylation events during the cold treatment in the winter rape (Filek et al 2006b). The importance of the first weeks of a prolonged exposure to cold was also suggested.…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…These results confirmed the authors' previous analysis, which suggested the presence of MSAP loci with changes in the methylation state specific for vernalization and a significant prevalence of demethylation events during the cold treatment in the winter rape (Filek et al 2006b). The importance of the first weeks of a prolonged exposure to cold was also suggested.…”
Section: Discussionsupporting
confidence: 91%
“…Seeds of two rapeseed cultivars, a winter ('Górczański', G) and spring type ('Młochowski', M), were germinated as described in Filek et al (2006b). Plants were grown in a growth chamber at 17/15°C (day/night, 16 h day) until the stage of a 5-leaf rosette and then transferred for 8 weeks (56 days) into 5/2°C (day/night, 16 h day) for vernalization.…”
Section: Plant Materials and Experimental Designmentioning
confidence: 99%
See 3 more Smart Citations